2006
DOI: 10.1111/j.1447-0756.2006.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing postpartum hemorrhage in Vietnam: Assessing the effectiveness of active management of third‐stage labor

Abstract: This study supports the value of AMTSL in reducing the incidence of PPH, shortening the third stage of labor, and reducing the need for additional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
(12 reference statements)
0
20
0
9
Order By: Relevance
“…In a meta-analysis of 17 studies, while the rate of post-partum haemorrhage varied between 4% and 51% without uterotonic treatment, it was shown that the rate of post-partum haemorrhage regressed to the following values with prophylactic oxytocin infusion, misoprostol treatment and ergometrine treatment, respectively: 0-32%, 1-45% and 0-37%. In the same study, the blood loss occurring with the administration of prophylactic uterotonic treatment was compared [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. It was found that this was reduced by an average of 151-499 mL in the patients administered with oxytocin, 155-433 mL in the patients administered with misoprostol and 149-476 mL in the patients administered with ergometrine.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 17 studies, while the rate of post-partum haemorrhage varied between 4% and 51% without uterotonic treatment, it was shown that the rate of post-partum haemorrhage regressed to the following values with prophylactic oxytocin infusion, misoprostol treatment and ergometrine treatment, respectively: 0-32%, 1-45% and 0-37%. In the same study, the blood loss occurring with the administration of prophylactic uterotonic treatment was compared [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. It was found that this was reduced by an average of 151-499 mL in the patients administered with oxytocin, 155-433 mL in the patients administered with misoprostol and 149-476 mL in the patients administered with ergometrine.…”
Section: Discussionmentioning
confidence: 99%
“…Secara statistik IMD mempunyai hubungan yang bermakna dengan jumlah perdarahan pasca salin, namun hasil penelitian ini menunjukkan bahwa semua perdarahan yang terjadi kurang dari 200 cc, baik pada ibu yang menjalani IMD maupun pada ibu yang tidak menjalani IMD. 9,18,19,20 Adanya isapan bayi pada puting susu ibu menyebabkan oksitosin akan keluar lebih banyak. Hal ini menguntungkan karena otot-otot polos rahim akan terus berkontraksi.…”
Section: Hasil Dan Pembahasanunclassified
“…Rata-rata perbedaan jumlah perdarahan pada kedua kelompok adalah -38,1 cc. Perbedaan ini secara statistik signifikan dengan p <0,05 (p = 0,000), 95% CI = 54, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]7. Variabel eksternal, baik usia, paritas atau pendidikan ibu, tidak memiliki hubungan yang signifikan dengan jumlah perdarahan postpartum dengan p> 0,05.…”
unclassified
“…
Reducing post-partum hemorrhage in Vietnam: Assessing the effectiveness of active management of third-stage labor Dear Editor, We were interested in the paper by Tsu et al 1 and support the use of oxytocin to manage third-stage labor (AMTSL) in a low-resource country when carried out by skilled attendants.We also agree that misoprostol is the proven efficacious drug for AMTSL in situations in which most women deliver without a skilled attendant especially in the developing countries. Misoprostol has a long shelflife, is stable, easy to administer (oral/rectal) and is very economical.
…”
mentioning
confidence: 98%